Next-generation sequencing-based BRCA testing on cytological specimens from ovarian cancer ascites reveals high concordance with tumour tissue analysis. Issue 3 (19th September 2019) - Fumagalli, Caterina; Rappa, Alessandra; Casadio, Chiara; Betella, Ilaria; Colombo, Nicoletta; Barberis, Massimo; Guerini-Rocco, Elena
Abstract : Background: With the approval of the poly (ADP-ribose) polymerase (PARP) inhibitor olaparib for newly diagnosed, breast cancer gene (BRCA)1/2 mutated, ovarian cancer women, the assessment of BRCA1/2 tumour status will be shortly required at the time of diagnosis. Aim: To investigate the feasibility of next-generation sequencing (NGS)-based BRCA tumour test on cytological specimens from ovarian cancer ascites. Methods: We evaluated the BRCA1/2 status on neoplastic ascites and corresponding tumour tissue of 11 patients with ovarian cancer, using the NGS 'Oncomine BRCA Research Assay'. Results: The NGS-based BRCA test on cytological samples had a success rate of 100%, with 11 of 11 concordant BRCA1/2 results between ascites and tumour tissues analyses, including two wild type samples and nine cases harbouring somatic or germline variants. Conclusion: BRCA test may be performed on ovarian cancer ascites, reproducing BRCA1/2 tumour status and representing a useful tool for clinical decision-making.